Towards a Theology in the Indian Context - Naluparayil, Jacob (Journal of Dharma, 1983)
Antony Mookentbottam M.S.F.S. Towards a Theology in the Indian Context Bangalore: Asian Trading Corporation, 1980, 350 pp.